L'inizio del cammino professionale I tirocini curricolari delle lauree pedagogiche, prima e durante la pandemia - Deiana, Salvatore; Secci, Claudia (UNICApress, 2023)
In recent decades, university degree programs have undergone a partial shift in their meaning and orientation, seeing an increase in the prominence of the professionalizing aspects of the training imparted. This partial shift in the direction of training has also entailed greater interaction with the world of work, with a view to an education in which the centrality of male and female students and the building of germinal foundations for their future were fundamental criteria. In this regard, the experience of curricular internships of first professional training was initiated and gradually increased in some degree programs. This occurred significantly in the three-year and specialized, later and still called master's degrees, of the educational and pedagogical field. The present volume aims to witness and analyze the specificity of these internships, as they developed in the courses of the relevant degrees at the University of Cagliari, in the period before the pandemic and during it. To do so, the theoretical-practical frame of reference is first outlined, and then the various actors involved, faculty, students and graduates, and representatives of the internship host institutions, are given the floor to narrate their experiences and to read and evaluate their main strengths and weaknesses.